SYSTEM AND METHODOLOGY OF WORK CONDUCTED THROUGH THE HEROES OF THE WORK IN THE TEACHING OF A WORK OF ART - Sayyora Matkarimova (Web of Journals Publishing, 2024)
This article describes the scientific-methodical approaches in the process of studying the character traits of the heroes of the literary work in the literature classes.
Keywords: Literature, school, artistic work, method, textbooks.